Implementation of Basic Entrepreneurship Management Skills to Achieve Independent Entrepreneurial Competence Among Students of Getsempena Bina Bangsa University - Risna Erita; Rita Novita; Siti Mayang Sari (Sean Institute, 2026)
This study aims to analyze the application of Basic Management Skill of Entrepreneurship in improving the independent entrepreneurial competence of students at Bina Bangsa Getsempena University. Basic Management Skill of Entrepreneurship is defined as a set of basic managerial skills that include planning, organizing, leadership, decision-making, and business control. These skills are used by students to manage their businesses systematically and independently. This type of research is a quasi-experimental study with a One Group Pre-Test–Post-Test design. The main problem of this study lies in the low independent competence of students in managing their businesses, so that intervention is needed in the form of the application of basic entrepreneurial management skills. The research sample consisted of 20 students who are active entrepreneurs and are members of the Bina Bangsa Getsempena University Business Incubator program. The results of this study show a significant increase in students' independent competence after the application of Basic Management Skill of Entrepreneurship. The N-Gain Score of 0.84 indicates a high increase category. Hypothesis testing using a Paired Samples T-Test with a significance result (2-tailed) of 0.0005 < 0.05, which proves a significant difference between the scores before and after treatment. This finding shows that basic entrepreneurial management skills significantly contribute to improving students' independent competence.